Enhancing Students' Writing Skills through Project-Based Learning with Digital Media Integration: An Experimental Study - Irwandi; Bafadal, Moh Fauzi; Mahsup; Ismail, Hijril (Forum for Linguistic Studies, 2024)
This study introduces an innovative approach by integrating Project-Based Learning (PBL) with digital media to improve Indonesian university students’ academic writing skills. Using a mixed-methods approach, the research involved 118 third-semester English students divided into an experimental group using the PBL model and a control group following traditional teaching methods. A quasi-experimental design was implemented, with pre-tests and post-tests assessing students’ writing performance. Surveys and open-ended responses provided qualitative insights into students’ perceptions of the intervention. The findings revealed a significant improvement in the writing skills of the experimental group, supported by statistical analysis that showed the significant improvement in the writing skills of the experimental group’s post-test scores (mean difference of 10.305, p < 0.001) compared to the control group (mean difference of 3.475, p < 0.001). Students expressed positive perceptions of the PBL approach, appreciating its interactive and collaborative elements. Thus, the integration of digital media with PBL proved effective in enhancing students’ writing abilities, fostering creativity, and promoting active learning. Overall, this study provides strong evidence for the benefits of integrating digital tools into project-based learning to enhance writing instruction and prepare students for the demands of the digital age.